Chronic Lymphocytic Leukemia (CLL): evaluation of AKT protein kinase and microRNA gene expression related to disease pathogenesis - Lorena Caixeta Gomes; Rodrigo Ribeiro Resende; Ricardo Cambraia Parreira; Cláudia Natália Ferreira; Edna Afonso Reis; Rita Carolina Figueiredo Duarte; Luan Carlos Vieira Alves; Sergio Schusterschitz da Silva Araújo; Maria das Graças Carvalho; Adriano de Paula Sabino (Universidade de São Paulo, 2022)
Abstract The present study evaluated 56 patients diagnosed with Chronic Lymphocytic Leukemia (CLL) and a control group of 44 clinically healthy subjects with no previous history of leukemia. Genetic expressions of AKT and microRNAs were evaluated by quantitative PCR (qPCR). A significant increase in AKT gene expression in patients when compared to controls was observed (p = 0.017). When the patients were stratified according to Binet subgroups, a significant difference was observed between the subgroups, with this protein kinase appearing more expressed in the B+C subgroup (p = 0.013). Regarding miRNA expression, miR-let-7b and miR-26a were reduced in CLL patients, when compared to controls. However, no significant differences were observed in these microRNA expressions between the Binet subgroups (A versus B+C). By contrast, miR-21 to miR-27a oncogenes showed no expression difference between CLL patients and controls. AKT protein kinase is involved in the signaling cascade that occurs with BCR receptor activation, leading to increased lymphocyte survival and protection against the induction of cell death in CLL. Thus, increased AKT protein kinase expression and the reduction of miR-let-7b and miR-26a, both tumor suppressors, may explain increased lymphocyte survival in CLL patients and may be promising markers for the prognostic evaluation of this disease.